Study on the bonding performance between basalt textile and concrete under freeze-thaw cycles. (April 2023) - Cai, Shixing; Lin, Jianhong; Fan, Kaifang; Chen, Yuanyi; Wang, Zeping
Highlights: The pull-out and four-point bending tests are performed to investigate the bonding performance of BTRC under freeze–thaw conditions. The freeze–thaw cycle will significantly decrease the bonding stress and flexural loading, presenting the formulas for calculating the ultimate flexural strength of BTRC under freeze–thaw cycles. SEM is employed in the micro-cracks and bonding performance analysis. The normalized strength degradation law was proposed to describe the freeze–thaw effects on BTRC. Abstract: Basalt textile-reinforced concrete (BTRC) is an environment friendly building material attracted wide attention in civil engineering. The investigation of the durability characteristic of the BTRC specimen is an important part of guiding the design of BTRC. In this paper, the tensile and flexural performances were investigated by the pull-out test and the four-point bending test with BTRC specimens under different freeze–thaw conditions. Meanwhile, the scanning electron microscope (SEM) is employed in the micro-cracks and bonding performance analysis. The results showed that as the number of freeze–thaw cycles increased, the peak and residual bonding stress are reduced, and the same for the ultimate flexural loading. The paper presents the formulas for calculating the ultimate flexural strength of BTRC under freeze–thaw cycles, and the difference in calculating results is less than 12% of the experimental results. The SEM images are shown that as the number of freeze–thaw cycles increased, the gap between the bonding surface was widened, which also well explains the degradation of bonding performance between fiber bundles and concrete matrix. And the normalized strength degradation law satisfies the function relation well.